Bayesian inference of a spatially dependent semi-Markovian model with application to Madagascar Covid’19 data - Angelo Raherinirina; Stefana Tabera Tsilefa; Tsidikaina Nirilanto; Solym M. Manou-Abi (PLoS ONE, 2025)
This article presents an approach to stochastic analysis of disease dynamics. We develop an explicit semi-Markovian model that accounts for spatial dependence, operating in discrete time over a finite state space. The model allowed us to have a propagation model conditioned by neighboring states and quantifies two key characteristics : spatial propagation timescales and propagation law in a region dependent on neighboring states. The model is inferred from data collected on the spread of Covid’19 in Madagascar’s 22 regions, using the Bayesian approach to get a better idea of model parameter values. The result has demonstrated the effect of neighborhoods on the propagation dynamics of diseases. We conclude with a discussion of potential future theoretical developments.